OPTIMIZING DRUG TREATMENT OF PATIENTS WITH CHRONIC GENERALIZED PERIODONTITIS USING A COMBINATION OF FLUOROQUINOLONES AND ORNIDAZOLE - Malik, N.E. (World of Medicine and Biology, 2012)
A comprehensive clinical study of 35 patients with chronic generalized periodontitis in age from 25 to 50 years. Along with the standard methods of clinical validation was determined by flow immunological parameters cytofluorimetry with the definition of subpopulations of cells that express CD3, CD4, CD8. Investigated the number of major lymphocyte subpopulations in gingival capillary blood. In chronic generalized periodontitis has been a shift of cellular immunity. Thus, the use of antimicrobial agents in chronic generalized periodontitis should be differentiated and consistent clinical and immunological stage of the process.
Keywords: periodontitis; treatment